Correlation between Reciprocal Teaching and Arabic Cognitive Learning Outcomes of Mts Dahlia Mantofani Students - Sri Wahyuni; Nurhadi; Nur Qomari (Tarling : Journal of Language Education, 2025)
One key indicator of successful learning is the achievement of students' learning outcomes. If students show improvement in their learning results, it indicates that the teaching and learning process has been effective. Therefore, to ensure a high-quality learning experience, teachers must possess the ability to implement appropriate teaching methods that align with the needs and characteristics of students in the classroom. This study aims to analyze the correlation between the application of reciprocal teaching learning and the cognitive learning outcomes of Mts dahlia mantofani students. The research method used is quantitative, researchers will calculate the relationship between variables using a correlational type of research. The data collection method is through interview, questionnaire, and test techniques. The population of this study were all seventh grade students at Mts dahlia mantofani totaling 48 students with a sample size of 24 students with the sampling technique used, namely cluster random sampling. The results showed that the correlation coefficient value between the variable application of reciprocal teaching method and cognitive learning outcomes amounted to 0.778**. Significance in the spearman correlation, shows a significance of 0.000 where the value is less than significance <0.05. Based on the explanation of the data analysis above, that the application of reciprocal teaching learning has a correlation relationship that is in the same direction / in line with student learning outcomes. And it can be concluded that the correlation between the variable learning application of reciprocal teaching method and students' cognitive learning outcomes is that it has a strong and significant correlation level relationship strength. Keywords : Correlation, Reciprocal Teaching Method, Cognitive Learning Outcomes